The Implementation of Character Education in Elementary Schools: an Evaluation Research - Widodo, Slamet; Yulianti, Yuni (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
The latest educational curriculum reform in Indonesia has foregrounded the implementation of character education policy and high order thinking skills in teaching and learning process. It attempts to create quality human resources that have sound characters and good skills. Despite its emphasis on the inculcation of character education, there has not been enough evaluation of its implementation particularly in elementary schools. This study, therefore, aimed at describing the implementation of character education policy in elementary shools in Surabaya. The method of this study was an evaluation research that used cluster random sampling to choose elementary schools in six districts out of 36 districts in Surabaya. Questionnaires and observation sheets were administered to elicit data which were then analyzed quantitatively and qualitatively from both primary and secondary resources. The result of this study elucidated that elementary schools in Surabaya have implemented character education policy. The schools have made character education as the school visions either explicitly or implicitly. However, there were still several cases that need improvements such as the lack of cooperation among the school stakeholders, the absence of standard measurement of the result of the character education implementation, and not supportive environment for the students.